2022
DOI: 10.1186/s40824-022-00278-2
|View full text |Cite
|
Sign up to set email alerts
|

Construction of magnetic nanochains to achieve magnetic energy coupling in scaffold

Abstract: Background Fe3O4 nanoparticles are highly desired for constructing endogenous magnetic microenvironment in scaffold to accelerate bone regeneration due to their superior magnetism. However, their random arrangement easily leads to mutual consumption of magnetic poles, thereby weakening the magnetic stimulation effect. Methods In this study, magnetic nanochains are synthesized by magnetic-field-guided interface co-assembly of Fe3O4 nanoparticles. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The scaffold not only needs a good antibacterial property but also should possess excellent tracheal regeneration function when it is applied to repair tracheal defects. The proliferation and live/dead staining of mBMSCs after coculturing with the composite scaffolds under 808 nm NIR light irradiation for 15 min were employed to evaluate the effect of heating and ROS on the cells surrounding the scaffold. As shown in Figure a, on the first day of culture, the number of mBMSCs for the ZnCN-Bi 2 S 3 /PLLA group was lower than that of the PLLA group under NIR light irradiation for 15 min, and more dead cells cultured on the ZnCN-Bi 2 S 3 /PLLA with NIR light irradiation were observed than for the PLLA group under 808 nm NIR light irradiation, indicating that the heating and ROS produced by the photothermal and photodynamic effects could hurt normal cells in some scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…The scaffold not only needs a good antibacterial property but also should possess excellent tracheal regeneration function when it is applied to repair tracheal defects. The proliferation and live/dead staining of mBMSCs after coculturing with the composite scaffolds under 808 nm NIR light irradiation for 15 min were employed to evaluate the effect of heating and ROS on the cells surrounding the scaffold. As shown in Figure a, on the first day of culture, the number of mBMSCs for the ZnCN-Bi 2 S 3 /PLLA group was lower than that of the PLLA group under NIR light irradiation for 15 min, and more dead cells cultured on the ZnCN-Bi 2 S 3 /PLLA with NIR light irradiation were observed than for the PLLA group under 808 nm NIR light irradiation, indicating that the heating and ROS produced by the photothermal and photodynamic effects could hurt normal cells in some scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…52,53 The magnetic Fe 3 O 4 nanoparticles can construct an endogenous magnetic microenvironment to mediate the osteogenic differentiation of stem cells via magnetic stimuli because of the diamagnetism of cell membranes. 10 However, the delivery of Fe 3 O 4 nanoparticles is still a problem on account of the aggregation. The incorporation of microgels and Fe 3 O 4 nanoparticles is anticipated to realize controllable release of Fe 3 O 4 nanoparticles.…”
Section: Biocompatibility Of the Hydrogel In Vivomentioning
confidence: 99%
“…In recent years, many studies have demonstrated that superparamagnetic Fe 3 O 4 nanoparticles can activate the receptor on the cell (such as ISCA1 or GPCRs) whether there is an applied magnetic field 6,7 . And then a series of signaling pathways will be modulated to enhance osteogenic differentiation 5,8–10 . Wang et al found that Fe 3 O 4 can upregulate long noncoding RNA INZEB2 (an essential factor for maintaining osteogenesis) and activate the classical mitogen‐activated protein kinase signal pathway, showing great potential in bone tissue regeneration 11,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biometals, including stainless steel and titanium alloy, possess distinguished mechanical properties and plastic toughness, and they can cause some complications and the release of toxic metal ions easily, and so on. [13][14][15][16][17] Bioceramics, including hydroxyapatite (HAP) and tricalcium phosphate (TCP), have great bioactivity, biocompatibility, and bone conductivity, but the major issue is their poor strength and low toughness. [18][19][20] Biopolymers, including poly (L-lactide) (PLLA) and poly (ε-caprolactone) (PCL), possess good biosafety, biodegradability, and formability, but their strength is insufficient, and their degradation products are acidic, easily resulting in aseptic inflammatory reaction.…”
Section: Introductionmentioning
confidence: 99%